2020
DOI: 10.1177/1747493020971970
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for lipid modification in patients with ischemic stroke or transient ischemic attack: A clinical guide by the Hellenic Stroke Organization and the Hellenic Atherosclerosis Society

Abstract: This document presents the consensus recommendations of the Hellenic Stroke Organization and the Hellenic Atherosclerosis Society for lipid modification in patients with ischemic stroke or transient ischemic attack. This clinical guide summarizes the current literature on lipid management and can be of assistance to the physicians treating stroke patients in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 65 publications
(71 reference statements)
0
8
0
2
Order By: Relevance
“…For such patients, it is suggested that lipid lowering treatment should be based on a personalized 10-year cardiovascular risk, estimated by the calibrated country-specific SCORE. 153 Figure 3 shows the proposed management of dyslipidaemia in IS.…”
Section: ‘C’: Cardiovascular Risk Factors and Comorbidities Optimizationmentioning
confidence: 99%
“…For such patients, it is suggested that lipid lowering treatment should be based on a personalized 10-year cardiovascular risk, estimated by the calibrated country-specific SCORE. 153 Figure 3 shows the proposed management of dyslipidaemia in IS.…”
Section: ‘C’: Cardiovascular Risk Factors and Comorbidities Optimizationmentioning
confidence: 99%
“…The second example is a guideline by the Hellenic Stroke Organization and Hellenic Atherosclerosis Society. 9 Authors reported that (1) patients with ischemic stroke or TIA should receive lipid-modifying treatment with a high-intensity statin (grade of recommendation/level of evidence, 1A) and (2) patients with ischemic stroke or TIA should be treated with an LDL-C target <55 mg/dL and at least 50% reduction of baseline LDL-C levels (1B). Finally, the European Stroke Organization (ESO)-Karolinska guideline 10 reported that "Statins should be used as a part of secondary prophylactic treatment after an ischemic stroke or TIA."…”
Section: Comments On Recent Guidelinesmentioning
confidence: 99%
“…Based on these results, recent guidelines have recommended the use of a high-dose statin with a low LDL-C target in patients with ischemic stroke. [8][9][10] However, there are concerns that this strategy may not be universally applied to all patients with ischemic stroke. In the HPS trial, 3 among participants with prior stroke, there was no apparent reduction in the incidence of recurrent stroke (rate ratio, 0.98; 95% CI, 0.79 to 1.22) in the simvastatin group, even if there was a significant reduction in the rate of any major vascular event (406 [24.7%] vs. 488 [29.8%], P=0001).…”
Section: Introductionmentioning
confidence: 99%
“…The authors discuss the benefit of statins and low LDL-C levels in patients with cardioembolic stroke as shown by several studies. However, there is no specific recommendation for this patient population 59 . Overall, no organization makes a definite statement or suggestion regarding LLT in patients with AF-related stroke.…”
Section: Overview Of Current Guidelines Regarding Llt In Patients With Strokementioning
confidence: 99%